Penggunaan daun singkong kering oven sebagai sumber vitamin a dalam ransum ayam petelur=The Utilization of Oven Drying Cassava Leaf as a Vitamin A Source in The Layer Ration - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1992)
Sixty layers at 22 weeks old were given 10 trial rations which have different level of cassava leaf to investigate an effect cassava leaf as vegetative vitamin A source of the egg production and egg quality. Each treatment consisted of 6 hens. To evaluate the egg fertility and egg hatchability were used 30 layers and 6 birds of male Harco strain 12 months old were received 6 trial rations. First experiment used factorial of variance analysis 3 (0%, 10%, 20% cassava leaf) X 2 (0%, 2,5% oil). Sub-experiment used factorial of variance analysis 2 levels of vitamin A source (vegetative, synthetic) X 2 levels of vitamin A (5581 IU, 11162 IU) X 2 level of oil (0%, 2,5%). Second experiment used an equal of variance analysis. The different effect of each factor were tested by Duncan's New Multiple Range Test. The results indicated that the increase level of cassava leaf improve the yolk colour, on the contrary the feed efficiency and egg production decrease. The oil supplementation could decrease the feed consumption, but the yolk colour improves. Compare with synthetic vitamin A source, the use of vegetative vitamin A source could decrease the feed efficiency, egg production and egg weight, but the colour of yolk improves. The increase of Vitamin A level in using of vegetative source could increase egg weight, but it decrease the feed efficiency and egg production. The oil supplementation in using of vegetative source of vitamin A could decrease feed convertion, on the contrary level 11162 HI vitamin A, the addition of oil could increase yolk colour intensity, but it reduces the egg weight. Interaction among three factors of treatment effected only on feed consumption. The egg fertility were not effected significantly by vegetative vitamin A source, but it significantly increased the egg hatchability.